Qi no tu i baba ni qwali (living down by the river): Impacts of flooding and mining on ecosystems and livelihoods - Varea, Rufino; Varea, Renata; Kant, Romitesh; Farrelly, Trisia (Frontiers in Marine Science, 2022)
A vast ocean rich with resources to maintain a sustainable livelihood surround Pacific Island Countries and Territories. In Fiji, coastal resources are a primary source of food, medicine, income and other necessities for livelihood security. Human-induced climate change places growing pressure on the quality of coastal resources due to the increased intensity and frequency of natural disasters like coastal erosion and flooding. Anthropogenic activities like coastal mining of earth minerals further threatens livelihood security with cumulative pressure on the coastal environment and its resources. This paper discusses the compounding impacts of mining in the flood-prone community of Vanua Votua in Ba (Fiji). They currently witness the degradation of their coastal environment and its resources (iqoliqoli). The people of Vanua Votua have a cultural and spiritual attachment to their coastal ecosystem as indigenous custodians. However, they are limited in their ability to conserve and protect their iqoliqoli due to an unfair legal duality of national coastal governance structures and processes between the state and indigenous custodians. We found that a central issue of coastal mining, governance, and the people’s livelihood vulnerabilities, is Fiji’s Mining Act [Cap 146] and associated environmental legislations and policies that consolidate much of the coastal governance authority with the state. The Fiji Mining Act is currently under review. This paper provides a timely case study using the Sustainable Livelihood Approach and the Vanua Research Framework, outlining the need for current and future legislation to be nuanced and sensitive to the realities of the local context.